The management centre IIUM MBA programme: the effectiveness of promotional mix to create customer awareness / Mohd Farihan Mustafa Kamal - Mustafa Kamal, Mohd Farihan (Faculty of Business and Management, 2008)
In this modern day business environment, the business world is getting more competitive and aggressive each day. Business competes with each other in order to boost sales by trying to come up with the best advertisement and promotion by using all tools available. Promotion is the basic prominent in making sure each local firm penetrate market and keep sustaining growth for existing market. However, Management Centre, IIUM which has limited resources, those promotions cannot be done in full swing by firm hence the objectives of promotions cannot be achieved or targeted. The purpose of this study is to identify the effectiveness promotional mix to create to create customer awareness.